Argüelles’ Preliminary Speech at the Constitution of 1812 and the Origins of Legal Historicism in Spain - Lloredo Alix, Luis M. (REVISTA DE HISTORIOGRAFÍA (RevHisto), 2015)
The traditional history and philosophy of law usually associates Spanish legal historicism with the Catalan Law School, which would have adopted this orientation as an intellectual tool to defend the existence of its “Foral Law” (Regional non-Castilian Law), particularly from the latter half of the 19th century. Likewise, it is accepted that legal historicism entered Spain via the German Historical School, particularly through its main advocate, Friedrich Carl von Savigny. In this paper, however, we will argue that Savigny and his School fell on fertile ground as legal historicism had already penetrated the topsoil. We will show how this historicist conception is outlined in the preliminary speech at the Constitution of Cádiz by Agustín de Argüelles.
Keywords: legal historicism; Historical School of Law; preliminary speech; spirit of the people Volsgeist; foral law